Effectiveness of fiscal policy measures in different public debt regimes - Gherghina, Rodica; Grecu, Robert-Adrian; Constantinescu, Carmen Maria; Duca, Ioana; Postole, Mirela Anca; Ciobănașu, Marilena (Journal of Business Economics and Management, 2024)
The aim of the research is to illustrate how the degree of effectiveness of fiscal policy measures varies depending on the level of public debt within a group of Central and Eastern European (CEE) states. To this end, a T-SVAR (Threshold Structural Vector Autoregressive) model was implemented, based on two regimes, calibrated as a function of the evolution of public debt. The results illustrate that, in most of the countries analysed, increasing government expenditure generates a stronger increase in economic growth under the low public debt regime in comparison with the situation at the level of the high public debt regime. Thus, the effectiveness of fiscal policy measures declines as the level of government debt rises. Another result obtained within the analysis highlights that the positive effect of public debt reduction on economic growth is more strongly felt in the higher public debt regime than under a low public debt regime. On the basis of these results, it is recommended that the CEE countries continue their efforts to reduce public debt in order to increase the effectiveness of fiscal policy measures.